Analysis of 400 kV pulse generator operation - Nikulin, E.S.; Belov, A.S.; Frolov, O.T.; Nechaeva, L.P.; Turbabin, A.V.; Zubets, V.N. (Вопросы атомной науки и техники, 2015)
The injector provides linac by 400 keV protons with energy stability ±0.1%, pulsed ion current - up to 100 mA, 50 Hz pulse repetition rate (PRR) with 200 μs duration. The results of the high-voltage pulse generator operation analysis which have been done with the aim of pulse repetition rate increasing up to 100 Hz are given. Special attention is paid to operation of the multi-cascade capacitance-diode discriminator with inductances. Інжектор постачає лінійний прискорювач протонами з енергією 400 кеВ, стабільністю енергії ±0.1%, тривалістю імпульсів 200 мкс і частотою повторення 50 Гц. Приводяться результати аналізу роботи генератора високовольтних імпульсів, проведеного з метою підвищення частоти проходження імпульсів до 100 Гц. Особлива увага приділена роботі багатокаскадного ємкістно-діодного дискримінатора з індуктивностями. Инжектор снабжает линейный ускоритель протонами с энергией 400 кэВ, стабильностью энергии ±0.1%, длительностью импульсов 200 мкс и частотой повторения 50 Гц. Приводятся результаты анализа работы генератора высоковольтных импульсов, проведённого с целью повышения частоты следования импульсов до 100 Гц. Особое внимание уделено работе многокаскадного ёмкостно-диодного дискриминатора с индуктивностями.